Impact of residue quality on the C and N mineralization of leaf and root residues of three agroforestry species - Vanlauwe, Bernard; Nwoke, O.C.; Sanginga, N.; Merckx, Roel (1996)
A laboratory incubation experiment with 15N labeled root and leaf residues of 3 agroforestry species (Leucaena leucocephala, Dactyladenia harto'i and Flemingia macrophylla) was conducted under controlled conditions (25 °C) for 56 days to quantify residue C and N mineralization and its relationship with residue quality. No uniform relation was found between the chemical composition of the above and below residues. The leucaena and dactyladenia roots contained more lignin (8 and 26% respectively) and less N (2.0 and 1.0% respectively) than the respective leaves (2 and 13% lignin and 2.9 and 1.4% N, respectively), whereas the differences between the lignin and N contents of the flemingia leaves and roots were not significant (4.6 and 3.0% lignin and 2.63 and 2.68% N, respectively). The leucaena leaves contained more polyphenols than the roots (6.4 and 3.6%), while the polyphenol content of the leaves and roots of the other residues was similar (5.0 and 5.1 % for dactyladenia and 4.0 and 3.5% for flemingia). Three patterns of N mineralization could be distinguished. A first pattern, followed by residues producing the highest amounts of CO2, showed an initial immobilization of soil derived N, followed by a net release of both soil and residue derived N after 7 days of incubation. A second pattern, followed by the flemingia leaf residues which produced intermediate amounts of CO2 and had an intermediate quality, showed no significant immobilization of soil derived N, and significant mineralization of residue N. A third pattern, followed by both low quality dactyladenia residues, showed a low release of residue derived N and a continued inmobilization of soil derived N. Residue C mineralization was significantly (p < 0.05) correlated with the residue lignin content, C-to-N ratio, and polyphenol-to-N ratio. The proportion of residue N mineralized (immobilized) after 56 days of incubation was significantly correlated with the residue N content (p < 0.01) and the C-to-N ratio (p < 0.05). The relations were quadratic, rather than linear. The ratio of the proportion of residue N mineralized (immobilized) over the proportion of residue C mineralized after 56 days was highly significantly correlated with the lignin content (p < 0.01 ) and C-to-N (p < 0.001), lignin-to-N (p < 0.01), polyphenol-to-N (p < 0.01) and (lignin+polyphenol)-to-N ratios (p < 0.0 I) in a linear way. This indicates that due to the low availability of the residue C, relatively less N is immobilized for the very low quality residues ((lignin+polyphenol)-to-N ratio: 29.7) than for the residues with a relatively higher quality ((lignin+polyphenol)-to-N ratios between 3.3 and 12.5).